Design strategies to rhodamine analogue fluorophores for near-infrared II biological imaging applications. (December 2021) - Liu, Chuangjun; Scott, Colleen N.
Abstract: Fluorescence imaging enables researchers to visualize a variety of biological tissues and processes with high spatial and temporal resolution. Near-infrared II (NIR-II) dyes are more desirable for imaging biological tissues than near-infrared I (NIR-I) dyes because of their reduced light scattering and tissue autofluorescence, as well as deeper tissue penetration. Whilst the development of NIR-II absorption and emission fluorophores is challenging, some advances have been made in this area. For example, cyanine derivatives and donor-acceptor-donor (D-A-D) structures with a benzobisthiadiazole core are reported as common NIR-II fluorophores. Besides these NIR-II fluorophores, NIR-II rhodamine analogues are also being realized for biological applications due to their ability to combine imaging with sensing. In this mini-review, we summarize the molecular engineering design strategies, optical properties, and applications of NIR-II fluorophores developed from rhodamine analogues. Finally, our outlook for the future of this field is presented. We believe this review will reveal the progress made, but also some challenges in developing NIR-II rhodamine analogues for effective and efficient sensing and imaging in biological tissues. Consequently, this review will interest researchers from biomedical, environmental, and other dye related communities. Graphical abstract: This mini-review summarizes the strategies to make NIR-II (900–1700 nm) fluorophores based on the rhodamine core, which furnish low background autofluorescence, reduced photon scattering, and higher resolution at the millimeter depth for bioimaging. These dyes are superior to rhodamine-based fluorophores in the visible (400–700 nm) and NIR-I (700–900 nm) regions. Image 1 Highlights: NIR II dyes are highly desirable for application in biological sensing and imaging due to deep penetration and high resolution. Xanthene-based days are desirable for biological applications due to their excellent photophysical properties. The D-A-D strategy to obtain NIR II xanthene-based dyes has successfully led dyes with labs over 1100 nm.